Aging‐related prognosis analysis of definitive radiotherapy for very elderly esophageal cancer. (2nd April 2018) - Zhou, Yong‐Chun; Chen, Li‐Li; Xu, Hong‐Bo; Sun, Qian; Zhang, Qi; Cai, Han‐Fei; Jiang, Hao
Abstract: Because of the exclusion for the patients more than 75 years (very elderly patients) in many clinical trials of esophageal cancer (EC), there is no consensus on prognosis and treatment for this population. We aim to evaluate the outcomes and aging‐related prognostic factors of definitive radiotherapy (RT) for very elderly EC patients. We retrospectively analyzed 149 very elderly EC patients consecutively treated between January 2015 and June 2016 by definitive intensity‐modulated radiotherapy (IMRT) with or without chemotherapy. The clinical outcome and toxicities were assessed, and the potential prognostic factors, such as nutritional risk index (NRI) and neutrophil–lymphocyte ratio (NLR), were analyzed statistically. The median follow‐up time for survivors was 22.5 months. The 2‐year overall survival (OS), local–regional failure‐free survival (LRFFS), and distant metastasis‐free survival (DMFS) were 51.6%, 54.7%, and 85.2%, respectively. Independent predictors for poorer OS were higher American Joint Committee on Cancer (AJCC) stage, lower NRI, and higher NLR value before RT. Meanwhile, the total dose (cutoff value 60 Gy) of planning gross tumor volume (PGTV) and chemotherapy was also identified as independent prognostic indicator for LRFFS and DMFS, respectively. 72 patients had treatment failure and 58 (80.6%), 6 (8.3%), and 18 (25.0%) patients had experienced local, regional, and distant failure, respectively. Few severe toxicities were observed. The conservative definitive RT with modern technique was effective for very elderly EC patients in short term with low rate and tolerable toxicities. Local residue or recurrence was the most common failure pattern. The aging‐related prognostic factors concerned nutrition and immune, such as NRI and NLR before RT, should be considered for use in future clinical practice. Abstract : The conservative definitive RT with modern technique was effective for very elderly esophageal cancer patients in short term with low rate and tolerable toxicities. Local residue or recurrence was the most common failure pattern. The aging‐related prognostic factors concerned nutrition and immune, such as nutritional risk index (NRI) and neutrophil–lymphocyte ratio (NLR) before RT, should be considered for use in future clinical practice.